﻿Efektivitas Balance dan Core Exercise untuk meningkatkanKeseimbangan Statis pada Kasus Stroke Hemiparese Sinistra - ﻿Pratama, ﻿Aditya ﻿Denny; Fatimah, Fatimah; Noviana, Mita; Pahlawi, Riza (UI Scholars Hub, 2022)
Stroke is a rapidly developing loss of brain function due to interruption of the blood supply to the brain. This can be caused by a blockage or bleeding in the blood vessels in the brain. The purpose of this study is to find out and understand how the effectiveness of balance and core exercise is to improve static balance in cases of left hemiparese stroke at Karmel Stroke Services. Of the various physiotherapy methods that can be done to overcome problems that can arise such as muscle weakness, balance disorders, posture disorders, and Activity Daily Living (ADL) disturbances in cases of left hemiparese stroke, in writing this final paper, the author chooses to use Balance and Core. Exercise. The writing method used in this case is an evidence-based case report with clinical questions.